Mapping Supply Chain Risks and Resilience Strategies For Startups Using The SCOR and FMEA Model: An Innovation Hub Perspective - Daisy, Armah Kemi; Slamet, Alim Setiwan; Cahyadi, Eko Ruddy (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Startups often encounter significant challenges in developing sustainable and efficient supply chain operations, particularly when resources are scarce and the business environment is in flux. Purpose: This study explores supply chain risks and resilience strategies within the vibrant startup ecosystem of the IPB (Institut Pertanian Bogor) Startup Innovation Hub in West Java, Indonesia. Design/methodology/approach: Utilizing a mixed-methods approach, the research includes questionnaires, interviews, and analytical techniques such as Failure Mode and Effect Analysis (FMEA) and Analytical Hierarchy Process (AHP) to identify and prioritize risks. Findings/Result: The findings reveal that effective supply chain resilience strategies for startups should focus on maintaining quality, enhancing flexibility and promoting sustainability. The analysis highlights that planning processes are particularly vulnerable, underscoring the need for robust forecasting and improved coordination. Innovation hubs are critical in supporting entrepreneurial growth by providing resources and facilitating networking. To navigate these challenges, the study recommends the implementation of a comprehensive Enterprise Risk Management framework and the cultivation of a risk-aware culture.Conclusion: By continuously refining their risk management strategies, startups can enhance their resilience, promote sustainability, and improve their capacity to manage supply chain disruptions, thereby boosting their growth potential in the innovation landscape. Originality/value (State of the art): This study is distinguished by its focus on the IPB Startup Centre innovation hub the research offers a cross-sectoral analysis of startups within a single innovation hub which allows the study to identify differences in supply chain risks across various startup types, contributing to a more inclusive understanding of risk management in entrepreneurial ecosystems. Keywords: innovation hub, startups, supply chain resilience, supply chain risk